2008
DOI: 10.1242/jeb.012211
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and mechanical determinants of bite force in bats: do muscles matter?

Abstract: SUMMARYBats are one of the most diverse groups of mammals and have radiated into a wide variety of trophic niches. Accordingly, the cranial structure in bats is unusually variable among mammals and thought to reflect specializations for feeding and echolocation. However, recent analyses of cranial structure, feeding behavior and bite force across a wide range of bats suggest that correlations between morphology and performance and/or ecology are not as clearcut as previously thought. For example, most of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(197 citation statements)
references
References 29 publications
11
183
2
1
Order By: Relevance
“…Thus the range of dietary niches available to stenodermatine bats is effectively broader than that of other phyllostomids. We have not demonstrated that increased bite force is associated with increased fitness in bats, but this is within the realm of possibility, as exposure to tougher foods has been identified as the agent of selection for Diversification and a new adaptive zone E. R. Dumont et al 1803 higher bite forces in a population of lizards [66]. There is only a single instance of convergent evolution of a morphological innovation linked to dedicated frugivory in bats (species in the family Pteropodidae), and that system has not been investigated in sufficient detail to draw close parallels.…”
Section: (B) Morphology Predicts Feeding Performance and Dietmentioning
confidence: 88%
“…Thus the range of dietary niches available to stenodermatine bats is effectively broader than that of other phyllostomids. We have not demonstrated that increased bite force is associated with increased fitness in bats, but this is within the realm of possibility, as exposure to tougher foods has been identified as the agent of selection for Diversification and a new adaptive zone E. R. Dumont et al 1803 higher bite forces in a population of lizards [66]. There is only a single instance of convergent evolution of a morphological innovation linked to dedicated frugivory in bats (species in the family Pteropodidae), and that system has not been investigated in sufficient detail to draw close parallels.…”
Section: (B) Morphology Predicts Feeding Performance and Dietmentioning
confidence: 88%
“…Third, a larger size directly results in higher bite force owing to absolutely greater jaw adductor physiological cross-sectional areas (e.g. [30,[54][55][56][57]). These higher bite forces would facilitate prey processing, as prey hardness scales positively with size [58] and carnivorous bats are osteophagous [23,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Empirically derived muscle stress values for chelonian cranial muscles are not available and 25Ncm -2 is commonly used by investigators attempting to determine theoretical whole muscleforce generation in vertebrates (e.g. Cleuren et al, 1995;Herrel et al, 1999;Herrel et al, 2008). Other verified muscle-stress values (20 and 30Ncm -2 ) were tested in an earlier study (Pfaller, 2009).…”
Section: Static Bite-force Modelmentioning
confidence: 99%
“…Other verified muscle-stress values (20 and 30Ncm -2 ) were tested in an earlier study (Pfaller, 2009). Bite-force generation was then estimated by developing a static equilibrium model of the forces generated by the jaw adductor muscles and the lever mechanics of the feeding system (Cleuren et al, 1995;Herrel et al, 2008;Huber et al, 2005;Huber et al, 2008). Photographs taken laterally and dorsally during muscle dissections were used to develop three-dimensional coordinate systems for each individual.…”
Section: Static Bite-force Modelmentioning
confidence: 99%